1999
DOI: 10.1562/0031-8655(1999)070<0254:camcot>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Molecular Characterization of the cDNA for the Brazilian Larval Click-beetle Pyrearinus termitilluminans Luciferase

Abstract: The larval click-beetle Pyrearinus termitilluminans elicits the phenomenon of luminous termite mounds in the central-west region of Brazil. The bioluminescence (BL) spectrum of this larva (lambda max = 534 nm) is one of the most blue-shifted reported among known luminescent Coleoptera. We have isolated mRNA from larval thoracic lanterns and constructed a cDNA library into a lambda ZAP II vector. An expression library was obtained after excision of the pBluescript plasmid. This library was screened by photodete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 12 publications
0
49
0
Order By: Relevance
“…To assess the timing of mitosis, our experiments required that we image luminescence so that we could visualize a cell splitting into daughter cells. We used green luciferase (PTGRm), identified in the luminescent Brazilian click beetle Pyrearinus termitilluminans, as our reporter because it is 21 times brighter than the widely used firefly luciferase (pGL3-basic) (37).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the timing of mitosis, our experiments required that we image luminescence so that we could visualize a cell splitting into daughter cells. We used green luciferase (PTGRm), identified in the luminescent Brazilian click beetle Pyrearinus termitilluminans, as our reporter because it is 21 times brighter than the widely used firefly luciferase (pGL3-basic) (37).…”
Section: Resultsmentioning
confidence: 99%
“…Although the active site of firefly luciferase was originally thought to be hydrophobic (15), more recent results suggest that it is amphiphilic (16). Click beetle luciferases, which produce different colours, have also been cloned (17,18). Mutagenesis studies identified the residues important for the bioluminescence activity and colours of these luciferases (19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…These fragments were inserted into the modified pcDNA4/V5-His (B) vector. (Nakajima et al, 2010;Viviani et al, 1999).…”
Section: Time-lapse Bioluminescence Imaging Of P53 Translocation Inmentioning
confidence: 99%